Zebrafish: A Model Organism for Studying Enteric Nervous System Development and Disease - Kuil, Laura E.; Chauhan, Rajendra K.; Cheng, William W.; Hofstra, Robert M. W.; Alves, Maria M. (Frontiers in Cell and Developmental Biology, 2021)
The Enteric Nervous System (ENS) is a large network of enteric neurons and glia that regulates various processes in the gastrointestinal tract including motility, local blood flow, mucosal transport and secretion. The ENS is derived from stem cells coming from the neural crest that migrate into and along the primitive gut. Defects in ENS establishment cause enteric neuropathies, including Hirschsprung disease (HSCR), which is characterized by an absence of enteric neural crest cells in the distal part of the colon. In this review, we discuss the use of zebrafish as a model organism to study the development of the ENS. The accessibility of the rapidly developing gut in zebrafish embryos and larvae, enables in vivo visualization of ENS development, peristalsis and gut transit. These properties make the zebrafish a highly suitable model to bring new insights into ENS development, as well as in HSCR pathogenesis. Zebrafish have already proven fruitful in studying ENS functionality and in the validation of novel HSCR risk genes. With the rapid advancements in gene editing techniques and their unique properties, research using zebrafish as a disease model, will further increase our understanding on the genetics underlying HSCR, as well as possible treatment options for this disease.